2016
DOI: 10.5194/hess-20-431-2016
|View full text |Cite
|
Sign up to set email alerts
|

An index of floodplain surface complexity

Abstract: Abstract. Floodplain surface topography is an important component of floodplain ecosystems. It is the primary physical template upon which ecosystem processes are acted out, and complexity in this template can contribute to the high biodiversity and productivity of floodplain ecosystems. There has been a limited appreciation of floodplain surface complexity because of the traditional focus on temporal variability in floodplains as well as limitations to quantifying spatial complexity. An index of floodplain su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…Ecosystem‐wide responses to multiple stressors in large floodplain rivers remain poorly understood (Tockner & Stanford, ). This is because of the inherent spatial heterogeneity (Scown et al, ) and temporal variability (Walker et al, ) of their hydrogeomorphology, governing processes, and ecological character. The enhanced complexity of large floodplain‐river ecosystems—where complexity is a function of spatial heterogeneity and temporal variability—challenges the construction of theoretical and applied models for these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem‐wide responses to multiple stressors in large floodplain rivers remain poorly understood (Tockner & Stanford, ). This is because of the inherent spatial heterogeneity (Scown et al, ) and temporal variability (Walker et al, ) of their hydrogeomorphology, governing processes, and ecological character. The enhanced complexity of large floodplain‐river ecosystems—where complexity is a function of spatial heterogeneity and temporal variability—challenges the construction of theoretical and applied models for these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Next, this approach incorporates subreach‐scale (<10 channel widths frequency) topographic variability because many hydrogeomorphic processes of ecological significance depend on specific patterns of topographic variability and associated habitat heterogeneity (MacWilliams, Wheaton, Pasternack, Street, & Kitanidis, ; Poff & Ward, ; Scown, Thoms, & De Jager, ). The local bankfull width at each location x i along the channel, w BF ( x i ), is given by Equation as a function of reach‐averaged bankfull width w BF and a variability control function f ( x i ), with a similar equation used to characterize vertical bed undulation that incorporates S : wBF()xi=wBF*f()xi+wBF. …”
Section: Methodsmentioning
confidence: 99%
“…Various components of the flow regime are responsible in shaping the geomorphological character of riverine landscapes (Schumm ), especially its physical heterogeneity (Scown et al. ). The geomorphological character of a riverine landscape is hierarchical, operating across multiple spatial and temporal scales (Thoms and Parsons , Thorp et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Dembkowski and Miranda , Scown et al. ). A limited number of studies have shown the influence of both hydrology and geomorphology on community composition (e.g., Hoeinghaus et al.…”
Section: Introductionmentioning
confidence: 99%